Perencanaan Pengelolaan Sampah Pasar Pelita SK 17 Desa Bangun Karya Kecamatan Rantau Rasau Kabupaten Tanjung Jabung Timur - Jonyyus Adi Putra; Guntar Marolop Saragih; Marhadi Marhadi (Jurnal Daur Lingkungan, 2018)
Management is a systematic, thorough and continuous activity which includes the reduction and handling of a substance or an object. Garbage is a remnant of human daily activities or natural processes shaped solid. This research is a research that aims to calculate waste generation and plan waste management in the SK17 lamp market planned for the next 10 years. The population in this study is all traders and settlements that exist in the market of Lamp SK 17 Bangun Karya Village, while the sample is the pedangang and the community around the market. Garbage generation for traders is 11, 875 liter / lapak / hari, shop 2,578 ltr / org / hari, settlement 0,969 ltr / org / hari. The volume of waste for 2016-2026 projected pedestrian street 926.25 ltr / day, store 959,016 ltr / day, settlement 2273,274 ltr / day. For Pelita SK 2015-2026 waste market planning requires 50 liters of organic reserves of 26 units for traders, 20 liters 93 units for settlements and 31 units for shops. Inorganic garbage collection is 26 units for traders stalls, 31 units for shops and 93 units for settlements each measuring 20 liters. Wastewater residual waste measuring 20 liters for traders' shanties amounted to 26 units, shops 31 units and settlements 93 units. Garbage B3 / B2 found only in the source of waste settlements, for waste b3 waste / B2 using bins measuring 20 liters amounted to 93 units.